2023
DOI: 10.1108/ejtd-04-2023-0054
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining entrepreneurial opportunity recognition and the significant role of education and training

Fredrick Muyia Nafukho,
Walid El Mansour

Abstract: Purpose The purpose of this paper was to determine the factors that enable entrepreneurial opportunity recognition and the significant role of education and training in enhancing opportunity recognition. Design/methodology/approach This paper follows a systematic literature review method to answer the research questions. A systematic literature review allows us to determine the work carried out to date, how it was done, assess literature and report all relevant research. The authors have used the Preferred R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Baron (2006) [93] states that opportunity recognition is contingent on the cognitive process. Creativity and entrepreneurial fervour were identified as the primary determinants in the opportunity recognition procedure by [94]. Opportunity identification emerged as a crucial component of cognitive competence in this current study, affecting entrepreneurial attitude.…”
Section: Discussionmentioning
confidence: 60%
“…Baron (2006) [93] states that opportunity recognition is contingent on the cognitive process. Creativity and entrepreneurial fervour were identified as the primary determinants in the opportunity recognition procedure by [94]. Opportunity identification emerged as a crucial component of cognitive competence in this current study, affecting entrepreneurial attitude.…”
Section: Discussionmentioning
confidence: 60%
“…While initial arguments suggested that skills, education level, and knowledge are crucial for recognizing and capitalizing on opportunities [24,30,32,33], it gradually was observed that people with relatively similar attributes performed differently, and some were not even interested in launching or running a business. Consequently, research has focused on understanding the various individual manifestations in terms of self-efficacy, reasoning ability, social skills, perseverance, experience, and education [34].…”
Section: Theoretical Background 21 the Role And Importance Of Busines...mentioning
confidence: 99%
“…Each option requires a level of alertness and knowledge of the current market to achieve success. The work by Nafukho and El Mansour (2023) seeks to identify ways to improve the identification of entrepreneurial opportunities within the market.…”
mentioning
confidence: 99%